PENERAPAN TEORI BELAJAR SKINNER DALAM UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA - Husnul Khatimah (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2025)
This research is a research action class (Classroom Action Research) aimed at improving the results of learning math kubus and balok material though penerapan teori belajar Skinner padasiswakelasVIII4 SMP Negeri 8Parepare. The subject of this research is grade VIII4 SMP Negeri 8 Parepare which totaled 25 people. This research was conducted in two cycles, each of which is three times the learning process and one time meetings conducted the test results of the study. The working procedures research each cycle lasting four stages, namely: (1), planning (2) the implementation of the action, (3) observations, and (4) Reflection. The techniques of collection data is used at this research is data about the results of the study were taken by giving it a test at the end of each cycle, whereas data about activity of students and teachers were taken by using the observation sheets during the learning process in the classroom. Based on the results of research and discussion for two cycles, then it can be concluded that the results of learning mathematics grade VIII4 SMP Negeri 8Parepare increase from cycle 1 to cycle II. This is indicated by: (1) increasing the average results of learning mathematic students is 66,52on cycle I became 83,36on cycle II; (2) improving learning completeness students math from cycle 1 to cycle II is 68%of the become 92%; (3) an increase at students activity which appropriate with learning is 54.84% in cycle I increased to 62,48%% in cycle II.